A phase II, double-blind, randomised, placebo-controlled study of BMS945429 (ALD518) in patients with rheumatoid arthritis with an inadequate response to methotrexate. Issue 7 (10th February 2012) - Mease, P; Strand, V; Shalamberidze, L; Dimic, A; Raskina, T; Xu, Li-An; Liu, Y; Smith, J
Abstract : Background: Interleukin 6 (IL-6) plays a key role in the inflammatory cascade in rheumatoid arthritis. BMS945429 is a humanised, monoclonal antibody that potently binds IL-6. Objective: To conduct aphase II study to determine the efficacy and safety of BMS945429 in patients with active rheumatoid arthritis and an inadequate response to methotrexate. Methods: Patients were randomised 1:1:1:1 to BMS945429 (80, 160 or 320 mg; administered intravenously) or placebo plus methotrexate during this 16-week, double-blind trial. The primary efficacy end point was the proportion of patients with a 20% improvement in American College of Rheumatology responses (ACR20) at week 12. Additional end points included ACR50 and ACR70 responses and 28-joint Disease Activity Scores (DAS28). Results: Of 127 randomised and treated patients, 116 completed the trial. ACR20 responders at week 12 were 81% (80 mg; p<0.0001 vs placebo), 71% (160 mg; p=0.0005 vs placebo), 82% (320 mg; p<0.0001 vs placebo) and 27% (placebo), respectively. By week 16, 14% (80 mg), 28% (160 mg) and 44% (320 mg) of BMS945429 patients were in DAS28 remission (DAS28 score <2.6). Statistically significant and clinically meaningful improvements in health-related quality of life (HRQoL) were reported in all active treatment groups. Administration of BMS945429 was associated with increases in liver enzymes and in serum cholesterol. There were no serious infections, infusion reactions or apparent immunogenicity. Conclusions: In this phase II study, BMS945429 was associated with rapid and significant improvements in disease activity and HRQoL in patients with active rheumatoid arthritis and an inadequate response to methotrexate.